Perubahan Perilaku Politik Luar Negeri Tiongkok terhadap Isu Laut Tiongkok Selatan - Darmawan, Arief Bakhtiar (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2018)
This article aims to explore China's foreign policy changes on the South China Sea dispute (SCS) since China has been willing to participate in regional or multilateral forums to date. This article argues that although the main characters and narratives of China?s foreign policy tend to be consistent, Chinese foreign policy behavior is changing. This study is a qualitative research that using non-numerical data sources, both primary and secondary. China's foreign policy behavior on the issue of SCS is divided into four phases. First, the passive and defensive phases. China still suspects that multilateral forums are a way of suppressing Chinese interests. Second, active phase. In this phase, China begins to believe in itself as a big and powerful country so as not to worry that multilateral forums will threaten its national security. Third, the initiative phase. China goes a step further by initiating some important multilateral initiative and multilateral breakthroughs in the long term project. Fourth, assertive phase. In this phase, China is involved in several incidents, consistent with their interests, while trying to refrain from initiating an open war. Through the change of foreign policy, China has adapted itself to contemporary international politics and has maintained its national interest in SCS.